Enhancement Students Pronunciation Ability through Phonetic Symbols at the Second Semester of English Department University of Muhammadiyah Sidenreng Rappang - Hasan, Hasan; Salma, Salma; Sadapotto, Andi; Usman, Usman (Maspul Journal of English Studies, 2021)
The objectives of the article were to find out: (1) To find out whether or not phonetic symbols increase pronunciation ability at the second semester students of University of Muhammadiyah Sidenreng Rappang. (2) To find out whether or not the students interested in the use of phonetic symbols in learning pronunciation at the second semester students of University of Muhammadiy ah SidenrengRappang. The researcher applied quasi experimental method using two groups namely an experimental and a control group. Both of groups were given pretest and posttest. The article was conducted at English Department of University of Muhammadiyah Rappang academic year 2019/2020. The researcher applied cluster sampling technique and the second semester is taken as the sample of the research with total numbers 22 students. This article was divided the number of sampling into to group namely Group A and B, where the group A and B consisted 11 students. The students’ result obtained and stated in the research, the researcher used t-test in inferential statistic through SPSS 21.0 program for Windows evaluation version to test the hypothesis. In pre-test, the researcher found that the t-test value was lower than the t-table (0.487 < 2.021). While in relation to the finding of post-test, the t-test value was higher than the t-table (3.948> 2.086). The result of the findings also showed that the students had high interest on the application of Phonetics Symbol materials in English pronunciation. It was proved by the mean score of the questionnaire was 85.91 which was classified into strongly interested category.